Sense of coherence does not moderate the relationship between the perceived impact of stress on health and self-rated health in adults with congenital heart disease. (December 2016) - Apers, Silke; Sevenants, Lien; Budts, Werner; Luyckx, Koen; Moons, Philip
Background: Adults with congenital heart disease seem to be more distressed than their healthy counterparts, which might render them even more susceptible to developing detrimental health outcomes. Previous research has confirmed the relationship between the perceived impact of stress on health and self-rated health. However, it remains unknown whether sense of coherence, a person's capacity to cope with stressors, moderates this relationship. Aim: This cross-sectional study aims to explore: the relationship between demographic and clinical characteristics, sense of coherence, and the perceived impact of stress on health; the relationship between the perceived impact of stress on health and self-rated health; and the moderating effect of sense of coherence in a sample of adults with congenital heart disease. Methods: Patients were recruited from the database of congenital and structural cardiology of a university hospital. The analytic sample included 255 patients (median age 35 years; 50% men). Data were obtained using self-report questionnaires and through medical record view. Univariate analyses and multiple regression analysis were conducted. Results: The perceived impact of stress on health was negatively associated with sense of coherence ( P <0.01), but there was no significant association with demographic or clinical characteristics. The perceived impact of stress on health and self-rated health were negatively associated ( P <0.001), but sense of coherence did not moderate this relationship. Conclusions: Our findings support the need for further research on the perceived impact of stress on health. Such insights can be valuable for developing interventions aimed at reducing the negative health consequences of stress in patients with congenital heart disease.